Sustainability of Portuguese fiscal policy in historical perspective - Carlos Jose Fonseca Marinheiro (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper analyses the sustainability of Portuguese public finances, making use of a long dataset with more than a full century of observations. The use of such a long dataset is appropriate because both unit root and cointegration tests require a long period of data. The sustainability testing procedure is based on unit root and cointegration tests. We find considerable evidence in favour of sustainability for the 1903-2003 period. The overall conclusion of sustainability for the 1903-2003 period is not maintained for the more recent 1975-2003 period, which is characterised by the largest GDP deficit ratios of our sample. This latter period appears to signal a shift to an unsustainable path in Portuguese fiscal policy. Hence, our results suggest that fiscal consolidation efforts must, in fact, be continued in Portugal.
Keywords: H60; E60; 330; fiscal sustainability; sustainability of public debt; intertemporal budget constraint; government deficits and debt; Portugal; Finanzpolitik; Haushaltsdefizit; Öffentliche Schulden; Verschuldungsrestriktion; Schätzung; Portugal